Maximize Property Sales and Purchase - Tawami, T; Suherman, G (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of writing this paper is to explain the benefits of using a website to accelerate the sale or purchase of property in Indonesia. The method of this writing is descriptive where the authors had examined the surrounding environment and interviews with several experts in the fields. The result of this study showed that the use of websites in the sale and purchase of property greatly increases the purchasing power and selling power of both sides of the website users both the seller and the buyer. The results of this study were expected to be more helpful to many sellers, buyers, and property brokers to know each other the best places to buy and sell ideal properties.